EMPLOYEE PERFORMANCE EVALUATED BASED ON PAY SYSTEM AND TEAM WORK - Abthal Albajili, Mochamad Rifqi; Munawaroh, Nuril Aulia (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH, 2023)
This study aims to determine the partial and simultaneous influence of the variable wage system and teamwork on employee performance at Kedai Papringan Cafe, Kediri City. This type of research is quantitative research with sample determination using a saturated sampling method where the entire population is used as a research sample with a sample size of 32 respondents. The data analysis technique used in this study uses statistical tests such as the Research Instrument Test, Classical Assumption Test, Multiple Linear Regression Analysis Test, Determination Coefficient Test, and Hypothesis Test using SPSS 25 for Windows. Based on the results of the analysis test used, the results of this study indicate that the wage system has a partially significant effect on employee performance with a t-count of 3.676 and a significant value of 0.001 and teamwork has a partially significant effect on employee performance with a t-count of 4.506 and a significant value of 0.000, as well as a simultaneous significant effect between the wage system and teamwork on employee performance with a F-count of 86.014 and a significant value of 0.000